In Vitro Culture of Muskmelon - Cucumis Melo Var. Birdie - Ismail, Zulaini (1989)

(untitled)
Several explants from Fl hybrid seeds and aseptically-germinated seedlings of muskmelon Cucumis melo var. Birdie, were tested for their capacity for plant regeneration through direct organogenesis in vitro. Excised cotyledons and - embryos from imbibed, ungerminated seeds were cultured on Murashige and Skoog (MS) medium containing 1.0 - 5.0 uM and 1.0-50.0 uM benzylaminopurine (BAP), kinetin, or isopentenyl adenine (2iP) respectively, in the presence or absence of 5.0 uM gibberellic acid (GA₃). Embryo explants produced callus on all media tested, and only 39 of cotyledon explants produced buds on medium containing 2.0 - 3.0 uM BAP. Unimbibed, testaless seeds were germinated aseptically on MS medium in the presence of 1.0 - 50.0 uM BAP, kinetin or 2 ip. On medium containing 3.0 uM BAP, 68% of cultures produced small buds in the region of the cotyledonary node within three weeks. The addition of GAl (5.0 uM) or naphthalene acetic acid (NAA) (0.1 - 1.5 uM) did not increase the percentage of cultures which produced buds. Cotyledonary nodes were subcultured to media containing the same (3.0 UK) or lower concentrations of BAP for two weeks and then to MS basal medium for another two weeks to allow further bud development and shoot elongation. The highest number of shoots per cotyl edonary node (9.7) was obtained when the first subculture medium contained 0.5 uM BAP. Individual shoots less than 1.0 cm, 1.0 - 2.5 cm and more than 2.5 cm in length, were tested for rooting ability in the presence of 3.0 uM IBA. The highest percentage rooting (49) occurred in shoots more than 1.0cm long. Further studies on root induction showed that the highest percentage of rooting (85% ), occurred when shoots 1.0 - 2.5 cm lonq were cultured in the light, on filter-paper bridqes in liquid, half-strength MS medium containing 2.0 uM NAA , without charcoal. Complete plantlets. fNere successfully transplanted to the qlasshouse and qrown in hydroponic culture. The plants flowered and produced normal fruit.